Mechanical and morphological behaviour of rice husk/prosopis juliflora reinforced bio composites. (2020) - Santhosh, M.S.; Karthikeyan, G.; Sasikumar, R.; Hariharan, R.; Mohanraj, R.
Abstract: Natural fiber composites with discrete filler reinforcements are extensively used over various monetary and engineering applications due to its colossal availability, and offhand processing methods. Over a few decades researchers worldwide directing on biodegradable and environmentally friendly natural fiber composites for various engineering applications. One such fiber prosopis juliflora (PJ), universally available around arid, semi-arid and Asian countries. All parts of the tree species have a wide range of usage. This present research focuses on the fabrication of Prosopis Juliflora composites filled with rice husk through book press compression mould technique and investigating its mechanical properties to grasp the filler ratio which possesses ultimate mechanical properties. Prosopis Juliflora/Rice husk/Epoxy hybrid composite (PREHC) samples with different volume fractions were prepared as per ASTM standard and its tensile, flexural, micro hardness and morphological behaviors were observed. Results reveal that the inclusion of rice husk significantly improves the mechanical behaviour of PREHC up to 45% than unfilled Prosopis Juliflora/Epoxy composites (PJEC). The proposed outcome of the research is suitable for structural and automobile engineering components.